Homeowner Fact Sheet: Citrus Canker - Megan M. Dewdney; Pamela D. Roberts; James H. Graham; Kuang-Ren Chung; Mongi Zekri (EDIS)
Revised! PP194, a 4-page illustrated fact sheet by M.M. Dewdney, P.D. Roberts, J.H. Graham, K.R. Chung, and M. Zekri, informs homeowners about this serious disease of citrus, its history, symptoms, spread, and control strategies. Published by the UF Department of Plant Pathology, October 2009.